Meta-analysis of the Intervention Effect of Cognitive Behavioral Therapy on Chemotherapy Anxiety Population - Fagang Ma; Yancan Wang; Wei Su; Yangyang Sun; Lin Cheng (International Journal of Biology and Life Sciences, 2026)
Objective This paper primarily analyzes the impact and extent of cognitive behavioral therapy (CBT) on anxiety levels in chemotherapy patients by reviewing and retrieving literature and relevant journals, aiming to provide theoretical support and practical references for clinical nursing. Methods A Meta-analysis was conducted, systematically retrieving literature from databases such as PubMed and CNKI. The time range was set from the initial inclusion date of each database to March 2026. Regarding studies on CBT intervention for anxiety in chemotherapy patients, content analysis and data extraction were performed to summarize the core intervention modules, implementation processes, and effect evaluation indicators of CBT. Results This study included 11 studies (n=11), with 2 in English and 9 in Chinese, totaling 1112 cases. The analysis showed that CBT, through its three core modules of cognitive restructuring, behavioral activation, and relaxation training, can effectively help chemotherapy patients recognize and alleviate their negative cognitions, thereby reducing anxiety. Most studies indicated that patients' anxiety scores decreased after CBT intervention, and patients also had a high level of acceptance towards this therapy. Conclusion Cognitive behavioral therapy has a significant effect on alleviating anxiety in chemotherapy patients, and its targeted intervention model can effectively improve patients' psychological state. However, in clinical practice, it is necessary to develop different intervention plans based on individual differences among patients. Future research could focus on the long-term effects of cognitive behavioral therapy.